2022
DOI: 10.20961/carakatani.v37i2.55164
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Flavonoids Content of Black Rice (Oryza sativa L. indica) with Compost Tea of Oyster Mushroom Waste

Abstract: The flavonoid compounds in black rice (<em>Oryza sativa</em> L. <em>indica</em>) are very important for health, they serve, for instance, as antioxidants and anticancer. Giving compost tea of oyster mushroom waste (COMW) can increase plant growth and flavonoid content to black rice. This research aims to determine the effectiveness of COMW to increase the growth and flavonoid content of black rice. This experiment using completely randomized design with single factor of five COMW concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Each cultivation style produces rice with a different quality index, indicating that land management changes rice quality. The organic rice field farming approach will increase soil and crop quality over time (Khoerunnisa et al, 2022). According to Mujiyo et al (2022), organic paddy fields produce better rice in Girimarto District, Wonogiri.…”
Section: Rice Quality Indexmentioning
confidence: 99%
“…Each cultivation style produces rice with a different quality index, indicating that land management changes rice quality. The organic rice field farming approach will increase soil and crop quality over time (Khoerunnisa et al, 2022). According to Mujiyo et al (2022), organic paddy fields produce better rice in Girimarto District, Wonogiri.…”
Section: Rice Quality Indexmentioning
confidence: 99%
“…Growing and developing roots can optimally absorb water as photosynthetic material (Hodge, 2014). Increased photosynthesis can increase the results of photosynthesis in the form of acylates translocated to grain and all parts of the plant to increase biomass (Khoerunnisa et al, 2022). The amount of carbon stored in plant biomass shows carbon dioxide (CO2) absorbed from the atmosphere.…”
Section: Carbon Total Sequestrationmentioning
confidence: 99%
“…Composting seems to be a lucrative area in agriculture biotechnology where agro-waste management is aimed at minimizing waste output, reducing environmental contamination, and boosting substrate recycling capacity [59]. The influence of compost tea from Oyster Mushroom Waste on the growth and the flavonoid content in the black rice was evaluated by Khoerunnisa et al [71]; the results displayed an increase in both the growing rate and flavonoid content depending on the treatments administered to the plants, in particular it was showed that the administration of compost tea of 45% lead to best rice growth, while the concentration of 35% lead to a best flavonoids content [71]. An example of the combined use of compost tea with other treatments is given by Lu et al [72], who investigated how hydroponically grown plants respond to UV light exposure and compost tea treatment.…”
Section: Influence Of Compost Tea On Nutrients and Bioactive Componen...mentioning
confidence: 99%
“…Compost tea Wild ginger Maximize accumulation of minerals, phytochemicals, and antioxidant [68] Compost tea and potassium humates Lettuce Increased concentration of minerals, primarily amino acids, saccharides, and antioxidants [69] Compost tea and humic acids Faba bean Increased nutritional content, total sugars, and crude protein [70] Compost tea from Oyster Mushroom Waste Black Rice Increased growth rate and flavonoid content [71] Compost tea and UV exposure Garnet Giant Mustard Increased nitrogen and mineral accumulation [72] Compost and vermicompost tea Cucumber (Cucumis Sativus L.) Increased antioxidant capacity [73] Compost tea Grape Increased N, P, K, and chlorophyll content in petioles, higher production, and total sugar and anthocyanin content in grape skins [74] Compost tea Blueberry Increased K concentration in leaves and fruit, increased Na content of leaves [75] Humic acids isolated from vermicompost Ananas Improved growth, increased nutrient content (N, P, K, Ca, Mg) [76]…”
Section: Crops Biostimulating Effect Citationsmentioning
confidence: 99%
See 1 more Smart Citation